Re-defining normal: bone mineral density in elite female athletes. Issue 4 (27th March 2011) - Cutti, P; Steele, R; Shrier, I; Garza, D; Meeuwisse, W; Bacharach, L; Matheson, G
Abstract : Background: College age female athletes are susceptible to decreased bone mineral density (BMD) which puts them at an elevated risk for poor bone health in the future. Objective: The primary purpose of this study was to compare site-specific and total body BMD of college-age female athletes across sports of varying impact level. Secondary objectives included (1) evaluating the relationship between BMD and menstrual, family bone health, and personal bone health histories; (2) to determine the best clinical predictors of BMD in this population. Design: Cross-sectional. Setting: NCAA Division I female athletes screened at university sports medicine centre. Participants: 265 (20.1±1.19 years, 66.5±10.9 kg, 1.7±0.09 m) college-age female athletes from 14 different sporting teams. Interventions: Personal and family health questionnaire, Total Body (TB), anteroposterior Spine (APS), Dual Femur (DF) BMD and Body Composition scans using GE Lunar iDXA. Main outcome measurements: Athletes were separated into three sport impact categories. BMD measurements were compared across the impact levels. Both stepwise regression and classification and regression tree analysis were conducted to determine significant predictors of BMD. Results: Athletes participating in low and moderate impact sports had significantly lower TB and site-specific BMD values when compared to high impact athletes (TB: High=1.24, Mod=1.18, Low=1.15; APS High=1.33, Mod=1.25, Low=1.21; DF High=1.25, Mod=1.12, Low=1.11). The BMD values for each secondary exposure were lower in those with history of abnormal menses (TB-1.19, APS- 1.24, DF- 1.17), previous stress fracture/reaction (TB-1.19, APS- 1.27, DF- 1.17), and poor family bone health (TB-1.18, APS- 1.26, DF- 1.16). Classification and regression trees (CART) analysis shows highest TB mean BMD was found in high impact athletes with LBM>50.9 kg. Conclusion: There is an ordinal relationship between sport impact level and BMD. Using CART analysis, gynaecological age, impact level and LBM are the best predictors of mean BMD.